2022
DOI: 10.1080/07853890.2021.1999494
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulmonary rehabilitation in patients with chronic obstructive pulmonary disease: a systematic review and meta-analysis of randomized controlled trials

Abstract: Objective The present systematic review and meta-analysis of randomized clinical trials (RCTs) aimed to investigate the effects of pulmonary rehabilitation in individuals with chronic obstructive pulmonary disease (COPD). Methods The RCTs of pulmonary rehabilitation programs published between 1999 and 2021 were retrieved from electronic databases (PubMed, Cochrane Library, and Embase). Two reviewers independently assessed the topical relevance and trial quality and extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 71 publications
(44 reference statements)
3
33
0
Order By: Relevance
“…Instead, we found an association between the endpoint occurrence and 6MWT which is commonly used as a measure of functional exercise capacity for the management of patients with moderate-to-severe pulmonary disease, capturing also manifestations of extra-pulmonary disorders, including cardiovascular disease, frailty, sarcopenia, cancer and others. 31 , 32 Although the 6MWT distance was consistently associated with symptoms and health-related quality of life across different disease groups, the relationships of this test with patient-reported outcomes were of weak to moderate strength. 33 Most of the studies in patients with chronic pulmonary diseases demonstrated that lower 6MWT distance is consistently associated with increased mortality, and – to a lesser extent – with hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we found an association between the endpoint occurrence and 6MWT which is commonly used as a measure of functional exercise capacity for the management of patients with moderate-to-severe pulmonary disease, capturing also manifestations of extra-pulmonary disorders, including cardiovascular disease, frailty, sarcopenia, cancer and others. 31 , 32 Although the 6MWT distance was consistently associated with symptoms and health-related quality of life across different disease groups, the relationships of this test with patient-reported outcomes were of weak to moderate strength. 33 Most of the studies in patients with chronic pulmonary diseases demonstrated that lower 6MWT distance is consistently associated with increased mortality, and – to a lesser extent – with hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic lung diseases and COVID-19 are leading causes of disease, death and disability globally 1 4 which entail a substantial burden on the individual 5 7 and healthcare systems. 8 , 9 Pulmonary rehabilitation (PR) is defined by the “National Heart, Lung, And Blood Institute” as a “supervised program that includes exercise training, health education, and breathing techniques for people who have certain lung conditions or lung problems due to other conditions” 10 is widely recognized as an important treatment for patients suffering from chronic respiratory diseases, 11 , 12 and has been recommended as a potential beneficial intervention for post-COVID-19 patients. 13 PR has been shown to provide statistically and clinically significant improvements in physical activity, exercise capacity, self-efficacy, and health-related quality of life (HRQoL), and a decrease in healthcare use in patients with lung diseases.…”
Section: Introductionmentioning
confidence: 99%
“…According to the British Thoracic Society guideline on pulmonary rehabilitation in adults, a rehabilitation program should include supervised, individualized, progressive exercise training [ 6 ]. COPD patients might benefit from various exercises [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%